The impact of hidden curriculum factors on professional adaptability - Danial Behmanesh; Shahram Jalilian; Akbar Babaei Heydarabadi; Mehrnaz Ahmadi; Nasrin Khajeali (BMC Medical Education)
Abstract Background The hidden curriculum encompasses the underlying values, norms, and behaviors conveyed indirectly through educational environments, significantly shaping medical students' professional adaptability. This study addresses the research gap in understanding the relationship between hidden curriculum components and professional adaptability among medical students at Jundishapur University of Medical Sciences. The innovation lies in quantifying this relationship using robust statistical methods. The objective was to evaluate how these hidden curriculum elements impact students' ability to adapt professionally. Methods This cross-sectional study involved 882 medical students, with a final sample size determined via Morgan's table, including 216 medical student during clerkship and 216 during internship,selected through census sampling. Data were collected using validated professional adaptability and hidden curriculum questionnaires and analyzed using Pearson correlation coefficients. Results Critical thinking showed the highest correlation with professional adaptability (r = 0.942, p < 0.001), followed by teaching methods (r = 0.874, p < 0.001). supportive environments (r = 0.809, p < 0.001) and Student–teacher interactions (r = 0.781, p < 0.001) also exhibited strong positive relationships. Other components, such as curriculum content and administrative structure, demonstrated moderate correlations. Conclusion These findings underscore the importance of the hidden curriculum in enhancing educational quality and professional training in medical education, highlighting the necessity for educators to integrate these elements consciously into their teaching strategies.